Cultivo de plantas medicinais e aromáticas em consórcio com hortaliças - Janini Tatiane Lima Souza Maia (2007)
The experiment was carried out from May to September 2007, in the field of conditions at Agriculture Science Institute of Federal University of Minas Gerais, Brazil. It was evaluated the performance production of lettuce, carrot, mint and basil in intercrop. It was used the randomized blocks chanced with seven treatments and six repetitions. The treatments had consisted of: single lettuce and intercrop with basil (Ocimum basilicum L.) and mint (Mentha x villosa H.), single carrot and intercrop with basil and mint, intercrop lettuce and carrot and single basil and mint.Two consecutive growing of lettuce were carried in the same conditions.Agroeconomic indicators were used to evaluate the efficiency of the intercropping systems: land equivalent ratio (LER), gross income and net (GI and NI), monetary advantage (MA), corrected monetary advantage (CMA), rate of return (RR) and profit margin (PM). In the first lettuce growing, the averages of contrasts showed advantage of the intercrop on single lettuce growing, with the basil as better company. In the second lettuce crop, single growing was better than intercrop. To the carrot the economic advantage has seen in monocrop system. The biomassproduction and essential oil of mint were not influenced by treatments. To the basin, only fresh matter was significative.